Nursing needs and prevention of complications after central venous catheterisation - Zujeva, Olga; Gierasimovič, Zita; Giedrimė, Lina (Slauga. Mokslas ir praktika, 2022)
Central venous catheterisation (CVC) is an invasive medical procedure with a high risk of complications. The role of the advanced practice nurse, who is aware of the types of CVC, potential risk factors and complication prevention tactics, is important in order to reduce the incidence of CVC complications. Objective. The aim of this article is to review the nursing needs and prevention of complications after central venous catheterisation. Materials and methods. Seventeen publications up to five years old on the topic were analysed. Articles from 2016 to 2021 were selected from PubMed, UpToDate and Google medical databases. All publications are in English, the text is full and free to access, and the year is no older than 2019. The selected publications describe complications associated with the CVC insertion procedure, choice of catheterisation site, recommendations for nursing staff on CVC care, and prevention of complications. Results. The mortality rate from bloodstream infection associated with CVC is approximately 12-25%. Because of the increased risk of infection, it is recommended to avoid femoral vein access. Inadvertent puncture of the artery, air embolism, bleeding and thrombosis are common complications. To reduce the incidence of mechanical complications, ultrasound should be used for diagnostic purposes during the insertion of the central venous catheter. The role of the nurse in the interprofessional team during the CVC insertion procedure is important. The nurse’s knowledge and clinical skills are one of the preventive measures, which is significant and important in controlling late infection and aseptic management of CVC. Conclusions. 1. Clinical practice of the nurse is based on the regulating legal acts, systematic training of the advanced practice nurse allows to manage the interventional procedure of central venous catheter placement. 2. Diagnostic control is used to reduce the risk of mechanical complications. Aseptic care of the central venous catheter is important for the prevention of infections.